Spatial Distribution and Source Apportionment of Heavy Metals in the Topsoil of Weifang City, East China - Li, Yan; Xu, Zhiqiang; Ren, Hanhan; Wang, Dong; Wang, Jian; Wu, Zhen; Cai, Pengjie (Frontiers in Environmental Science, 2022)
The distribution of heavy metals in topsoil can have a significant impact on human health. A total of 1, 556 samples were collected from the topsoil of Weifang, China. Various indices, including the pollution index (PI), the Nemerow integrated pollution index (PN), and the potential ecological risk index (RI), were used to analyze the heavy metal pollution levels. The sources of heavy metals were analyzed using the positive matrix factorization (PMF) model. The results are as follows: (1) the ecological risk level of Cu, Pb, Zn, Ni, Cr, and As in the study area is relatively safe, but the ecological risk level of Cd and Hg is relatively high, leading to an increase in the ecological risk level of heavy metals in the study area and (2) the PMF results show that there are six main sources of the eight heavy metals. Cr and Ni come from soil parent material and nonferrous metal industrial activities; As is closely related to fossil fuel (coal)-related industrial activities; Cu originated from diesel fuel-related transportation and agricultural machinery activities; Pb is derived from gasoline transportation activities; Hg is closely related to the application of pesticides in agricultural production; Cd and Zn originated from organic fertilizers used in agricultural activities.